Planning a Successful Field Trip - Keith G. Diem; Ben Knowles (EDIS)
Field trips can be great experiences for youth to learn project content and life skills. Field trips also contribute to the experiential learning philosophy of 4-H. This document includes some suggestions to make a field trip fun, safe, and educational. This 3-page fact sheet was written by Keith G. Diem and Ben Knowles, and published by the UF Department of 4-H Youth Development, July 2014.